EKSISTENSI PERPUSTAKAAN SEKOLAH DI ERA TEKNOLOGI INFORMASI (STUDI KASUSPEMANFAATANPERPUSTAKAAN SEKOLAHDI SMA NEGERI 1 SURAKARTA) - Isdhiega Arya Subiyantara (Jurnal Analisa Sosiologi, 2018)
The objectives of research were to find out the students’ perception on school library, to find out the effect of information technology development on the existence of school library in SMA Negeri 1 Surakarta, and to find out the school’s attempt in maintaining the existence of school library in SMA Negeri 1 Surakarta. This research employed a descriptive qualitative method with case study. The primary data source was obtained from informants consisting of deputy of head master for curriculum area, deputy of headmaster for infrastructure area, librarian, students, and teachers. Meanwhile, the secondary data source included profile, document, or school archive. The sampling techniques used were purposive sampling and snowball sampling technique. Techniques of collecting data used were in-depth interview, direct observation and document collection. To validate the data, data triangulation technique was used. The result of research showed that the students’ perception on library was affected by their perception on the completeness of library infrastructure. The students with independent learning pattern perceived positively the existence of school library by utilizing it actively as learning source and information source useful for their self development. Meanwhile the students rarely visiting the library tended to treat library pragmatically, i.e. as the place where they printed their assignment. The more rapidly development of technology made library reformed service by holding automation system to facilitated the service to users. The school’s attempt of maintaining the existence of school library was to cooperate actively with many parties such as government, students and teacher as users, and librarian. Keywords: School Library, Existence, Technology Development AbstrakTujuan dari penelitian adalah untuk mengetahui persepsi mahasiswa di perpustakaan sekolah, untuk mengetahui efek dari pengembangan teknologi informasi tentang keberadaan perpustakaan sekolah di SMA Negeri 1 Surakarta, dan untuk mengetahui sekolah mencoba dalam mempertahankan keberadaan perpustakaan sekolah di SMA Negeri 1 Surakarta.Penelitian ini menggunakan metode kualitatif deskriptif studi kasus.Sumber utama data Diperoleh dari informan terdiri dari wakil kepala sekolah untuk area kurikulum, wakil kepala sekolah untuk infrastruktur daerah, pustakawan, siswa dan guru.Sementara itu, sumber data sekunder termasuk profil, dokumen, atau sekolah Arsip.Teknik sampling yang digunakan adalah purposive sampling dan teknik sampel bola salju.Teknik pengumpulan data yang digunakan adalah wawancara mendalam, pengamatan langsung dan koleksi dokumen.Untuk memvalidasi data, data Triangulasi teknik digunakan.Hasil penelitian menunjukkan bahwa persepsi mahasiswa Perpustakaan dipengaruhi oleh persepsi mereka pada kelengkapan Perpustakaan infrastruktur.Siswa dengan pola belajar mandiri dianggap positif keberadaan perpustakaan sekolah dengan memanfaatkan aktif sebagai belajar sumber dan sumber informasi yang berguna untuk pengembangan diri mereka.Sementara itu para siswa yang jarang mengunjungi perpustakaan cenderung memperlakukan Perpustakaan pragmatis, yaitu sebagai tempat di mana mereka dicetak tugas mereka.Lebih cepat pengembangan teknologi dibuat Layanan Perpustakaan direformasi oleh memegang otomatisasi sistem untuk memfasilitasi layanan kepada pengguna. Sekolah upaya mempertahankan keberadaan perpustakaan sekolah adalah untuk bekerja sama secara aktif dengan banyak pihak seperti pemerintah, siswa dan guru sebagai pengguna, dan pustakawan. Kata Kunci: Pengembangan teknologi Perpustakaan, keberadaan, sekolah